1-(4-Chlorobutanoyl)-3-(2-nitrophenyl)thiourea - Ngah, Nurziana; Kadir, Maisara; Yamin, Bohari M.; M. Yusof, M. Sukeri (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C11H12Cl2N2OS, contains two crystallographically independent molecules with different conformations: the benzene ring and the thiourea fragment form dihedral angles of 74.32 (11) and 89.39 (11)°. One amino group in each molecule is involved in intramolecular N—HO and intermolecular N—HO hydrogen bonding: the latter links pairs of independent molecules into dimers. In the crystal, weak N—HS interactions link these dimers into chains propagating along the c axis.